ANALISIS PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE) DAN TINGKAT INFLASI TERHADAP PER (PRICE EARNINGS RATIO) PADA PERUSAHAAN MANUFAKTUR BIDANG FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rizki Aditya Septadi; Rodhiyah Rodhiyah; Wahyu Hidayat (Universitas Diponegoro, 2013)
Indonesian capital market development is rapidly since the 1990s, making the need for increased securities trading analysis. PER a favorite because it is quite easy to understand for investors and prospective investors. PER is part of the ratio of the market determines how the market gives the value or price of a company. Ability profitable a company as one of the main consideration sources of most investors to invest. Ability of high profits can be demonstrated with profitability ratios such as Return on assets (ROA) and Return on Equity (ROE). The rate of inflation causes economic conditions of a country shaking.This study aimed to determine the effect of ROA, ROE and Inflation to PER. This type of research is explanatory research or explanation. The population in this study is the financial statement data manufacturing company engaged in the field of Food and Beverage is listed in the Indonesia Stock Exchange in 2010 and 2011 and a sample of the study was 15, a manufacturing company engaged in the field of Food and Beverage listed on the stock exchange Indonesia. Data collection in this study was done by non participant observation. In the data analysis using the classical assumption test, simple linear regression and multiple regression test with SPSS program.Based on the survey results revealed that the ROA, ROE and Inflation positive and significant effect on PER, either partially or simultaneously. Simultaneously, the variable ROA, ROE and inflation effect on PER of 39.3 percent. This suggests that the overall return on assets (ROA), Return on Equity (ROE) and the Food and Beverage company Inflation 2010-2011 period can be a calculation in the determining PER.